Cohort profile: l'Actuel Pre-Exposure Prophylaxis (PrEP) Cohort study in Montreal, Canada. Issue 6 (27th June 2019) - Greenwald, Zoë R; Maheu-Giroux, Mathieu; Szabo, Jason; Robin, Judith Alexia B; Boissonnault, Michel; Nguyen, Vinh-Kim; Thomas, Réjean
Abstract : Purpose: The l'Actuel PrEP Cohort was established to monitor the uptake, effectiveness, safety and changes in sexual risk behaviours among individuals receiving pre-exposure prophylaxis (PrEP) for the prevention of HIV. This prospective dynamic cohort is based at Clinique médicale l'Actuel, a large sexual health clinic located in Montreal, Canada. Participants: Since the cohort inception in January of 2013 through June 2018, 2156 individuals consulted for PrEP as participants in the l'Actuel PrEP Cohort. Median age was 35 years (IQR: 29–44 years) and the majority (96%) were men who have sex with men. Among 1551 individuals who initiated PrEP care, the median duration of follow-up was 9.2 months (IQR: 3.7–19.6), with substantial variation based on year of cohort entry. The l'Actuel PrEP Cohort contains both daily and intermittent 'on-demand' PrEP users and has the largest reported population of intermittent PrEP users (n=406) in North America. Findings to date: No incident HIV infections have occurred among individuals using PrEP over 1637 person-years of follow-up. However, retention in PrEP care is essential as three individuals who discontinued PrEP subsequently acquired HIV, translating to an HIV incidence of 3.9 cases per 100 person-years (95% CI: 1.3 to 12.1). Among a sample of participants with 1 year of follow-up before and after PrEP initiation (n=109), a moderate increase in sexually transmitted infections was observed following PrEP start. Future plans: The l'Actuel PrEP Cohort continues to grow with new participants starting PrEP monthly and extended follow-up for existing users. The cohort data will be used for ongoing monitoring of PrEP and for population-level modelling of the impact of PrEP on HIV incidence in Montreal.